APLIKASI PENGINDERAAN JAUH DAN SISTEM INFORMASI GEOGRAFIS UNTUK EVALUASI KESESUAIAN LAHAN HUNIAN TETAP DI KECAMATAN CANGKRINGAN KABUPATEN SLEMAN - , RIANA SEPTIASTUTI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The eruption happened in 2010 caused thousands of houses have been damaged in Cangkringan District. The government determines the permanent settlement scattered in Cangkringan. The objectives of this research are (1) mapping the level of the suitability of hunian tetap recommended by government based on physical, social, and economics aspect required by using remote sensing data and geographic information system. (2) examining the influence of social and economic parameters to the determination of the land suitability for permanent settlement by using field data and geographic information system analysis. This research uses matching method. The parameters used on is the land suitability for permanent settlement of physical and socio-economic parameters. Physics parameters that used in this research are consist of slope, the affordability of water sources, and zoning vunerabilty of hazard. Affordability of education facilities, health facilities,economic facilities, and the centre of working area are used as social-economic parameters The result of this research indicated that the houses in Cangkringan District mostly includes on land suitability class S1 include huntap Pagerjurang, Banjarsari, dan Gondang. Land suitability class S2 including huntap Jetis Sumur, Batur, Dongkelsari, Randusari, and Kuwang. Land suitability class S3 including huntap Karangkendal, Gading, and Plosokerep.